2013
DOI: 10.1037/a0034575
|View full text |Cite
|
Sign up to set email alerts
|

Attentional bias for nondrug reward is magnified in addiction.

Abstract: Attentional biases for drug-related stimuli play a prominent role in addiction, predicting treatment outcome. Attentional biases also develop for stimuli that have been paired with non-drug reward in adults without a history of addiction, the magnitude of which is predicted by visual working memory capacity and impulsiveness. We tested the hypothesis that addiction is associated with an increased attentional bias for non-drug (monetary) reward relative to that of healthy controls, and that this bias is related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
125
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(147 citation statements)
references
References 47 publications
19
125
3
Order By: Relevance
“…This result is in line with former research: Anderson et al [37, 38] and Nielsen et al [11] compared BIS-11 scores in abstinent OD patients, patients enrolled in maintenance therapy, and healthy controls and found significantly higher impulsivity in OD patients. However, the difference between abstinent and maintained patients was not significant.…”
Section: Discussionsupporting
confidence: 82%
“…This result is in line with former research: Anderson et al [37, 38] and Nielsen et al [11] compared BIS-11 scores in abstinent OD patients, patients enrolled in maintenance therapy, and healthy controls and found significantly higher impulsivity in OD patients. However, the difference between abstinent and maintained patients was not significant.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, the attentional biasing effects of reward are not limited to drugrelated stimuli. In a cohort of opiate-addicted participants, monetary reward was seen to bias attentional processing (Anderson et al, 2013). Together, these findings suggest that ACC governs attentional control generally under the influence of reward-related cues.…”
Section: Discussionmentioning
confidence: 61%
“…Finally, Della Libera and Chelazzi (2009) demonstrated not only that attentional processes are influenced by rewards but also that this effect is long-lasting, occurring several days after the end of the learning phase and when rewards are no longer at stake. These data open interesting perspectives for rehabilitation of patients with attention disorders (see Lucas et al, 2013;Olgiati et al, 2016) or abnormal reward-seeking behaviors (see Anderson et al, 2013a).…”
Section: Figmentioning
confidence: 98%
“…Hickey and collaborators (2010b) reported, for instance, that healthy subjects with reward-seeking personalities, assessed by the BIS/BAS inventory, showed a larger modulation by reward of an intertrial priming effect. Using a reward association paradigm, Anderson et al (2013a) demonstrated that the attentional capture by previously high-rewarded stimuli in a subsequent visual search task was greater in patients receiving methadone maintenance treatment for opioid dependence. This effect was also shown in patients with HIV, and correlated with prior HIV-related risk-taking behavior.…”
Section: Individual Differences In Reward Sensitivitymentioning
confidence: 99%